Penyuluhan Pengendalian Mutu Produk Susu Terfermentasi Skala Home Industry pada Pondok Pesantren Raudhatul Madinah-Batu - Ningsih, Wahyuni; Naryono, Eko; Moentamaria, Dwina; Takwanto, Anang; Hakim, Arif Rahman (Edumedia Solution, 2024)
Fermented milk in the form of yogurt is a type of processed milk that is beneficial for the body's health. This product could become a home industry scale entrepreneurial product for the Raudhatul Madinah Islamic boarding school, Batu. Quality products whose quality is maintained over time will certainly be a special attraction for customers. This service activity aims to provide education about quality control of fermented milk products at the Raudhatul Madinah-Batu Islamic Boarding School. The methods used are lectures, discussions, questions and answers, and mentoring. The form of yogurt quality control is outlined in the SOP document, then pH tests and organoleptic tests (sour, aroma, texture) are also carried out on the yogurt products produced. Then, participants were asked to fill out a partner satisfaction questionnaire with service activities. The results of the questionnaire showed that 62% of participants agreed and 37% strongly agreed that they were satisfied with the service activities carried out.